1995
DOI: 10.1074/jbc.270.28.16701
|View full text |Cite
|
Sign up to set email alerts
|

OpuA, an Osmotically Regulated Binding Protein-dependent Transport System for the Osmoprotectant Glycine Betaine in Bacillus subtilis

Abstract: Exogenously provided glycine betaine can efficiently protect Bacillus subtilis from the detrimental effects of high osmolarity environments. Through functional complementation of an Escherichia coli mutant deficient in glycine betaine uptake with a gene library from B. subtilis, we have identified a multicomponent glycine betaine transport system, OpuA. Uptake of radiolabeled glycine betaine in B. subtilis was found to be osmotically stimulated and was strongly decreased in a mutant strain lacking the OpuA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
230
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(241 citation statements)
references
References 59 publications
8
230
2
Order By: Relevance
“…The transcription initiation site of the gbsA gene was determined by primer extension analysis with a synthetic primer (5Ј-TGCAATTTCTTCTTGATTAA ATGGG-3Ј) complementary to the gbsA mRNA (bp 1358 to 1334 [see Fig. 3]) and avian myeloblastosis virus reverse transcriptase as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription initiation site of the gbsA gene was determined by primer extension analysis with a synthetic primer (5Ј-TGCAATTTCTTCTTGATTAA ATGGG-3Ј) complementary to the gbsA mRNA (bp 1358 to 1334 [see Fig. 3]) and avian myeloblastosis virus reverse transcriptase as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
“…Glycine betaine can be accumulated directly from the environment through three osmotically controlled uptake systems (25): OpuD, a single-component transporter, and OpuA and OpuC (ProU), multicomponent transport systems that are related to the binding protein-dependent transport system ProU from Escherichia coli (25,26,34).…”
mentioning
confidence: 99%
“…3). A search for consensus sequences of the osmoresponsive promoters for the compatible solute transport systems proU, prop and o p u A (Mellies et al, 1994(Mellies et al, ,1995Kempf & Bremer, 1995) revealed no matches. As several osmoregulated genes in non-halophiles, including the genes for the biosynthesis of trehalose, are known to be under the control of as-dependent promoters (Strram & Kaasen, 1993;Gordia & Gutierrez, 1996;Manna & Gowrishankar, 1994;Mellies et al, 1995), we also conducted a search for consensus sequences of these (Strram & Kaasen, 1993), but were unable to find any matches.…”
Section: Ectoine Synthesizing Capacity Of Deletion Derivatives Of Posmllmentioning
confidence: 99%
“…Comparisons with sequences deposited in GenBank indicated that clone pUC-AS17 contained about one-third of the 5' end of the f i ORF at the erm-proximal end of Tn917, and, at the em-distal end of the transposon, the complete ylxM gene. Upstream from ylxM, sequences were found that were homologous to the proU/opuA operon of B. subtilis (Kempf & Bremer, 1995), specifically to the 3' half of the proV/opuAA gene and to unlinked segments of the complete downstream proW/opuAB and proX/opuAC genes. The proU/opuA operon encodes an osmoregulated ABC-dependent transport system involved in the uptake of compatible solutes including glycine betaine.…”
Section: Cloning and Sequence Analysis Of The Sat Locusmentioning
confidence: 99%